(untitled) (Intent Research Scientific Journal, 2023)
Central Asia is currently the most rapidly developing region on the planet, both economically and in terms of other factors such as demography — population size and growth, the creative component — development of new technologies, products, and services, and the cultural field.India is a rising superpower that is establishing itself as an Asian powerhouse. India is likewise attempting to establish itself as a key regional player in Central Asia. The efforts of India in the Shanghai Cooperation Organization (SCO) reflect its own perception of regional dynamics and the country’s place in them. In this context, it is worthwhile to examine India’s regional politics, current potential, and factors impeding its implementation.